2017
DOI: 10.1038/srep45295
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptome analysis provides insights of key gene(s) involved in steroidal saponin biosynthesis in medicinally important herb Trillium govanianum

Abstract: Trillium govanianum, an endangered medicinal herb native to the Himalaya, is less studied at the molecular level due to the non-availability of genomic resources. To facilitate the basic understanding of the key genes and regulatory mechanism of pharmaceutically important biosynthesis pathways, first spatial transcriptome sequencing of T. govanianum was performed. 151,622,376 (~11.5 Gb) high quality reads obtained using paired-end Illumina sequencing were de novo assembled into 69,174 transcripts. Functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…The downstream genes of steroidal saponin biosynthesis in leaf (SQS, CPI1, CyP5G1, FK, HDY1 and SMO2) and fruit (SQLE, SMT1, SMO1, DWF5, UGT80B1 and β-glucosidase) also showed higher expression level. These results indicate that steroidal saponins biosynthesis mainly occur in leaf and fruit tissues (Singh et al 2017).…”
Section: Trillium Govanianummentioning
confidence: 76%
“…The downstream genes of steroidal saponin biosynthesis in leaf (SQS, CPI1, CyP5G1, FK, HDY1 and SMO2) and fruit (SQLE, SMT1, SMO1, DWF5, UGT80B1 and β-glucosidase) also showed higher expression level. These results indicate that steroidal saponins biosynthesis mainly occur in leaf and fruit tissues (Singh et al 2017).…”
Section: Trillium Govanianummentioning
confidence: 76%
“…Each individual sample had about 63 million sequence reads. Previous studies demonstrated that approximately 30 million reads are sufficient to detect more than 90% of annotated genes in mammalian genomes ( Wang et al, 2011 ; Lee et al, 2013 ; Singh et al, 2017 ). The relatively high number of sequence reads generated in this transcriptome study indicates that our data are adequate for identification of DE genes.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of fenugreek (T. foenum graecum Linn) [35] and the rhizomes of D. zingiberensis are also important sources of DG. In addition, Trillium govanianum and Costus speciosus contain around 2.5% and more than 2.12% of DG, respectively [36][37][38]. DG is mainly generated by the hydrolysis of steroidal saponins in the presence of a strong acid, base, or enzyme catalyst [39].…”
Section: Sources Of Diosgeninmentioning
confidence: 99%